EVALUATION OF THE SCHOOL - BASED CURRICULUM IN MATHEMATICS SUBSTANCE LEARNING GROUP OF DAONAIROI SCHOOL, SONGKHLA, BY USING TYLER MODEL - Kamnerdphon, Phakapapha; Chutima , Thutsaro; Boonprakarn, Kettawa (Journal of MCU Nakhondhat, 2023)
This research paper aims to study evaluate the learning curriculum of mathematic department at Daonairoi School in Songkhla Province, using Tyler’s assessment model, which was a qualitative research. The target group of the research were school administrators, teachers, parents and students. The study involved 216 participants using cluster sampling. The research tools consisted of interview forms and questionnaires in terms of educational objectives, organization of learning experiences and academic achievement. The statistical analysis, utilizing percentage, mean, and standard deviation, was employed to evaluate the data. The research showed that the learning achievements were consistent with the objectives of the mathematics learning curriculum. The research outcomes indicated that 1) the aim of the curriculum was consistent and comprehensive to develop the students in arithmetic, concluded from school administrators, teachers and parents, as assessed by 18 people, the assessment result showed ( ) of 4.45 and a S.D. of 0.55, which was at an excellence level, 2) the organizing of learning experiences to make students gain knowledge, the assessment results showed ( ) of 4.55 and a S.D. of 0.62, which was at the excellence level. 3) the academic achievement examination results in the mathematics subject in the academic year of 2022 compared with the school action plan for the academic year of 2022. The mean score ( ) of 86.41 percent achieved at a quality level of 3 or above can be categorized in an excellent level. The desired outcomes have been attained in accordance with the specified goals and objectives. The results of the research derived from group discussion consisted of school administrators, teachers, parents, and students showed that the students, who had taken courses in mathematics and possessed a good and fundamental grasp of the subject matter in mathematics, would be able to apply the knowledge for further study at a higher level and in various competitive examinations.